How Does Foreign Equity Right Impact Manufacturing Enterprise Innovation Behaviors? Mediation Test Based on Technology Introduction - Shan Cen; Lianshui Li; Weijun Cui (Discrete Dynamics in Nature and Society)
The impacts of FDI (foreign direct investment) on the innovation of Chinese local enterprises have always been the focus of attention, but few studies have explored the impacts of foreign shareholding on enterprise innovation behaviors through the micro level. Based on the survey data regarding the manufacturing sector of China enterprises conducted by the World Bank in 2012, this paper conducts an empirical study on the relationship between foreign shareholding and enterprise innovation behaviors. The research findings include two aspects; that is, (1) foreign shareholding has significantly positive impacts on enterprise innovation behaviors; (2) technology introduction plays a complete mediating effect in foreign shareholding and enterprise innovation behaviors. On the basis of considering sample selective bias and endogenous problems, the propensity score matching (PSM) method is further applied to evaluate the impacts of foreign shareholding on enterprise innovation behaviors. After putting the endogenous problems and sample selective bias under control, the above conclusions are still robust. Thus, under the current complicated international situation, enterprises should be encouraged to attract foreign investment under moderate control, with a view to accelerating the promotion of enterprise innovation activities through the technology introduction brought about by foreign shareholding.